Assessing the Effect of Career Adaptability on Employee Engagement through Public Service Motivation: Study of Civil Servants in Indonesia - Handayani, Dwi; Abbas, Hafid; Nurjanah, Siti (Migration Letters, 2023)
This study aimed to examine the effect of civil servant career adaptability on employee engagement mediated by public service motivation. This study adopts the theory of job demand resources and takes the perspective of organizational behavior theory to explain personal resource variables. The proposed hypothesis was tested by conducting a partial least square - a structural equation model on data collected from 599 millennial civil servants in Indonesia. This study found that career adaptability, directly and indirectly, affects employee engagement with public service motivation as a mediating variable. This study offers academics significant insight in providing empirical evidence of organizational behavior theory for a direct relationship between career adaptability and public service motivation. The implication of this research for human resource management in government organizations is awareness of designing programs to increase the career adaptability of millennial civil servants, so that it will have significant impact on public services because of their motivation and engagement to stay in the public sector.